Modeling PVC-coated polyester as a hypoelastic non-linear orthotropic material. (1st February 2017) - Jekel, Charles F.; Venter, Gerhard; Venter, Martin P.
Abstract: A hypoelastic non-linear orthotropic material model was characterized for two different PVC-coated polyesters from uniaxial tests in the warp, fill, and 45° bias yarn directions. Ultimately the non-linear orthotropic material model fails to capture the full behavior of PVC-coated polyester. Thus the determination of material parameters depends upon which experimental response is the most important for the model to capture. Two methods are presented for determining different parameters for the non-linear orthotropic material, such that each method captures a particular aspect of the material's response better than the other method. The first approach derives the stiffness moduli as a function of strain from the experimental stress–strain response of the uniaxial tests. The second approach utilizes an inverse analysis, powered by an optimization routine, to find the best material parameters such that the experimental load–displacement response is matched in the finite element (FE) model. Additional the Poisson's effect was investigated, and the transverse uniaxial behavior is presented.